The Thing which Traces Itself: Limits and Apories of Sensible Appearing from Early Phenomenology - Johnson, Felipe (2021)
This paper aims to investigate the presence of sensible things in the light of the works of early phenomenology. For this purpose, a reflection will be made from the problems that some thinkers of Gotinga circle outlined in the context of Husserl’s theses about Abschattung. Thus, we will distinguish between things and their sensible stroke, detecting the possibilities of their mutual phenomenal connection and detachment. By this way, a triple relationship will be identified in which the empirical thing appears, composed of sensitive qualities, sensations of the perceiver subject and its spatial location, in order to examine which of these instances explains the necessary link between sensitive stroke and thing as a possibility of its actual appearance in reality. It will be concluded that there is an a priori adjustment between qualities and physical properties that will allow to understand the presentative function of the sensible stroke of things.